English Daily Conversation at Islamic Boarding School in Improving Speaking Skill of EFL Student - Annisa Najiyah Aulia; Muhamad Sofian Hadi; Lidiyatul Izzah (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This research aims to know the effect of English daily conversation program in improving students’ speaking skill. The method used in this study was Quantitative method with Pre Experimental research design by using both Pre-Test and Post-Test as the instruments of collecting the data. The research was conducted at Nurul Ilmi Darunnajah 14 Islamic Boarding School, Serang-Banten. The sample technique used was Purposive Sampling, in which one class of 7th E grade were choosen as the sample. The data was analyzed statistically by using t-test. The result of this study showed; the mean of students’ Pre-test was 59.85, while the mean of students’ Post-Test was 7.2. the statistic calculation revealed that the result of t-calculation (tcal)>t-table (tt), in which t-calculation (t-cal) obtained was 4.03 while t-table (tt) was 2.093 with a significant (0.05) which means that t-cal was higher than tt. Thus, alternative hyphothesis (H1) was accepted and the null hyphothesis (H0) was rejected. Based on these results it can be concluded that English Daily Conversation Program improved students’ speaking skill.